2023
DOI: 10.1111/jgs.18424
|View full text |Cite
|
Sign up to set email alerts
|

A diet modification intervention for older women with fecal incontinence

Abstract: Overcoming reluctance to accept home-based support from an older adult perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Previous studies have examined the relationship between dietary patterns and FI but did not consider the levels of dietary inflammation. For instance, a single-arm, pre-post controlled prospective study of 39 elderly women with FI found that patients' mean Vaizey score (a scale of FI severity) decreased by 2.3 points ( p = 0.01) after the administration of a structured dietary intervention, and 29 (74.4%) patients perceived an improvement in symptoms ( 29 ). In addition, based on previous research, Menees et al recruited 43 patients with FI and compared the efficacy of a low FODMAP diet (LFD) for 4 weeks with psyllium 6 g/d.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the relationship between dietary patterns and FI but did not consider the levels of dietary inflammation. For instance, a single-arm, pre-post controlled prospective study of 39 elderly women with FI found that patients' mean Vaizey score (a scale of FI severity) decreased by 2.3 points ( p = 0.01) after the administration of a structured dietary intervention, and 29 (74.4%) patients perceived an improvement in symptoms ( 29 ). In addition, based on previous research, Menees et al recruited 43 patients with FI and compared the efficacy of a low FODMAP diet (LFD) for 4 weeks with psyllium 6 g/d.…”
Section: Discussionmentioning
confidence: 99%